Trueman's UGC-CSIR JRF/NET LifeSciences (Biology) - Pramod Singh (New Delhi Dhanika Publishing, 2016)
Singh. P's Trueman's UGC CSIR-NET Life Sciences 1st Edition is a comprehensive book for CSIR - UGC NET/JRF aspirants. The book comprises of model question papers and exclusive questions for the students. In addition, there are multiple chapters that help in giving you a clear understanding of various concepts. This book is essential for candidates applying for CSIR - UGC NET/JRF and other competitive exams.
Keywords: Life Science